The Existence of Legal Principles and The Changing Times: Challenges and Adaptations in The Formation of Laws and Regulations - Tanti Kirana Utami; Ega Puspita; Fauzan Hidayat, Shidqi; Pradipa, M Rafly; Dwi Lestari, Retno; Syahdan Fauzi (Indonesian Journal Publisher, 2025)
The existence of legal principles in the formation of legislation plays a crucial role in modern legal systems. This article examines the challenges and adaptations faced in maintaining the relevance of legal principles amidst rapid changes in society, using a qualitative normative juridical research method. This method focuses on legal norms found in legislation and norms that are living and evolving within society. The aim is to understand how the existence of legal principles has evolved in the context of rapid societal changes, reaching the present era, and how the legislative process reflects adaptation to these changes, as well as to explore examples of legislation that successfully integrate legal principles with the needs of modern society. The findings of this study show that the existence of legal principles relies not only on their ability to uphold timeless fundamental principles but also on their capacity to transform according to the context of the times. By understanding the challenges and opportunities present, legal principles can remain relevant in addressing societal needs and global developments.